How terrorists think about the economic impact of attacks - Silke, Andrew (Pool Reinsurance (PoolRe), 2019)
It has long been recognised that terrorism can be a remarkably effective low cost form of conflict. For modest outlays on the part of perpetrators, terrorist violence can inflict disproportionately high economic costs. The potential for heavy economic impacts was a key factor behind the formation of Pool Re in the UK and other terrorism reinsurance schemes internationally.
Keywords: terrorism; terrorist decision-making; ideology; terrorist target selection